The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.ijo.0803364
|View full text |Cite
|
Sign up to set email alerts
|

Altered insulin-mediated and insulin-like growth factor-1-mediated vasorelaxation in aortas of obese Zucker rats

Abstract: Objective: Insulin and insulin-like growth factor-1 (IGF-1) have vasorelaxant effects in vivo, which is dependent on nitric oxide (NO) production. The aim of this study was to investigate the vasorelaxant responses mediated by insulin and/or IGF-1 in aortas of obese Zucker rats. Methods: The thoracic aortas of eight lean and eight obese Zucker rats (6 months old) were isolated for vasorelaxation analysis. Insulin-induced and IGF-1-induced vasorelaxant responses were evaluated by the isometric tension of aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Moreover, insulin and IGF-1 have been found to be involved in the development of many cardiovascular diseases, such as hypertension and diabetes mellitus (Goke & Fehmann, 1996;Vecchione et al 2001;McCallum et al 2005). Our laboratory had also reported that decreased insulin-induced vasorelaxation appeared to be countered by the increased IGF-1-induced vasorelaxation in obese rats (Yang et al 2007). In the present study, significant impairment of insulin-and IGF-1-induced vasorelaxation was found in spontaneously hypertensive rats.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, insulin and IGF-1 have been found to be involved in the development of many cardiovascular diseases, such as hypertension and diabetes mellitus (Goke & Fehmann, 1996;Vecchione et al 2001;McCallum et al 2005). Our laboratory had also reported that decreased insulin-induced vasorelaxation appeared to be countered by the increased IGF-1-induced vasorelaxation in obese rats (Yang et al 2007). In the present study, significant impairment of insulin-and IGF-1-induced vasorelaxation was found in spontaneously hypertensive rats.…”
Section: Discussionsupporting
confidence: 60%
“…However, the differential actions of insulin and IGF-1 contributing to cardiovascular diseases are not totally understood. Altered vascular function mediated by insulin and IGF-1 has been reported in some cardiovascular diseases, such as hypertension and obesity (Vecchione et al 2001;McCallum et al 2005;Yang et al 2007). Specifically, one study indicated that the attenuation of phenylephrineinduced constriction by insulin/IGF-1 was dysfunctional in hypertensive rats (McCallum et al 2005).…”
mentioning
confidence: 99%
“…Based on our data that IGF1R expression is upregulated in the vasculature of diabetic animals, we propose that hybrid receptor formation may contribute to vascular insulin resistance and pathology in vivo . This is supported by data showing that insulin-induced vasorelaxation in aortas of obese rats is significantly decreased, whereas IGF-1-induced vasorelaxation is profoundly increased, compared with that in lean rats 32. Similarly, IGF1R is upregulated and IGF-1-mediated aortic relaxation is increased after induction of diabetes by streptozotocin in rats 33…”
Section: Discussionmentioning
confidence: 64%
“…59 IGF-1 can stimulate NO production from endothelial and vascular smooth-muscle cells, indicating a vascular protective function. 60 IGF-1 also has antiapoptotic and neuroprotective effects. 61 In addition, serum IGF-1 levels are correlated significantly with muscle strength and physical performance.…”
Section: Growth Hormonementioning
confidence: 99%